2019
DOI: 10.1007/s10869-019-09648-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Employee Motivation for Work-to-Nonwork Integration Behavior: a Reasoned Action Approach

Abstract: This study investigates individual and organizational factors that motivate employees to enact the work role in the nonwork domain (work-to-nonwork integration behavior). We argue that implications of work-to-nonwork integration may be better understood by learning more about the reasons why employees perform integration behavior. Based on the reasoned action approach (RAA), we examined four antecedents of employee integration behavior: individuals' attitudes toward integration (integration preference), percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 58 publications
2
31
0
2
Order By: Relevance
“…First, although boundary management behaviours relate to individuals’ preferences, our findings support that these behaviours may be constrained by the overarching job. In this study, we specifically identified and examined level of responsibility and job structure as job characteristic variables that had received prior theoretical and/or empirical investigation within the work–family literature; however, more work is needed to better understand additional aspects of the work environment that may play a role in enacted boundary management, including pressure from supervisor (Capitano & Greenhaus, 2018), social support from coworkers and supervisors, job involvement (Byron, 2005; Michel et al, 2011), and workplace norms (Palm, Seubert, & Glaser, 2019). Further investigations of the evolution of work characteristics across one’s career trajectory (i.e., the potential for increased responsibility and decreased structure as one advances in roles) would also be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…First, although boundary management behaviours relate to individuals’ preferences, our findings support that these behaviours may be constrained by the overarching job. In this study, we specifically identified and examined level of responsibility and job structure as job characteristic variables that had received prior theoretical and/or empirical investigation within the work–family literature; however, more work is needed to better understand additional aspects of the work environment that may play a role in enacted boundary management, including pressure from supervisor (Capitano & Greenhaus, 2018), social support from coworkers and supervisors, job involvement (Byron, 2005; Michel et al, 2011), and workplace norms (Palm, Seubert, & Glaser, 2019). Further investigations of the evolution of work characteristics across one’s career trajectory (i.e., the potential for increased responsibility and decreased structure as one advances in roles) would also be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Motivation represents the level of employee's ambition to perform the work disregarding his personal happiness. Motivation in management represents the way with which, a manager supports productivity and effectiveness of employees (Palm et al, 2020;Lejsková et al, 2017;Crandall, 2016). Many managers are persuaded that motivation comes out of their personal character; however, a good motivation consists mainly of the right dealing with employees, rewarding and creation of conditions for work (Renninger & Hidi, 2015).…”
Section: Theoretical Developmentsmentioning
confidence: 99%
“…According to the theory, three primary factors influence individuals' behavioral intention, which in turn predicts their actual behavior: the individuals' attitude towards the behavior, subjective norms to (not) perform the behavior, and their perceived control over the behavior (Ajzen, 1991;Fishbein & Ajzen, 2010). Transferred to the context of boundary management, empirical studies underline that boundary management behavior is indeed predicted by individuals' attitude towards the behavior as reflected in boundary management preferences (e.g., Methot & LePine, 2016;Powell & Greenhaus, 2010;Palm et al, 2020). Further, indicators of perceived behavioral control such as boundary control, job autonomy, or boundary flexibility-ability were shown to be related to boundary management behavior (e.g., Matthews et al, 2010;Palm et al, 2020;.…”
Section: Antecedents Of Bidirectional Boundary Management Behavior: the Role Of Availability Expectationsmentioning
confidence: 99%
“…Or conversely, employees can avoid dealing with nonwork matters at work by turning off push notifications for nonwork communication but turn on push notifications for workrelated communication after hours. Yet, studies on boundary management enactment often focus on work-nonwork segmentation behavior (i.e., the degree to which individuals actually segment work from nonwork domains), omitting nonwork-work segmentation behavior (i.e., the degree to which individuals actually segment nonwork from work) (e.g., Kubicek & Tement, 2016;Palm et al, 2020). Hence, although well-established in theory (Clark, 2000;Kossek & Lautsch, 2012), the bidirectional nature of boundary management behavior is often disregarded.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation